Macroporous thermosensitive poly(HEMA-coNIPAAm) hydrogels for controlled drug delivery application - Setiyorini, Yuli (Indonesian Journal of Pharmacy, 2010)
Controlled  delivery  systems  of  a  predetermined  dose  over  a  sustained period  have  been  used  to  overcome  the  shortcomings  of  conventional  dosage forms. This is because the controlled drug delivery system can provide sustained therapeutic  level  of  drug  concentration  without  toxicity  and  convenience  for patients. It would be more beneficial and ideal if the drug could be delivered by a  device  that  would  respond  to  external  environmental  change.  Therefore,  the correct  amount  of  drug  would  be  released  upon  the  stimulation  of  such  a temperature change. The purpose of study is synthesis  of macroporous thermal responsive  poly(HEMA-co-NIPAAM)  hydrogels  by  free  radical  polymerization  for controlled drug delivery applications. Effect of varying water and HEMA-NIPAAm ratio  in  the  monomer  mixture  were  resulted  interconnected  macroporous structure.  From  the  result,  5HEMA15NIPAAm  was  showed  the  most  rapid responsiveness  in  swelling  ratio,  polymer  volume  fraction,  swelling  and deswelling  kinetics.  The  high  drug  loading  capacity  was  achieved  at  or  below ambient  temperature,  whilst  the  release  profile  was revealed  sustain  release  of conventional  anti-inflammatory  drug;  prednisolone  21  hemisuccinate  sodium salt.  In  general,  incorporating  appropriate  amount  of  water  and  HEMA-NIPAAm ratio can improve the swelling properties, drug loading capacity and drug release profile, which can be use for sustained release of various medication.Key words: macroporous, thermosensitive hydrogel, controlled drug delivery application